Annexin A6 and Late Endosomal Cholesterol Modulate Integrin Recycling and Cell Migration - García-Melero, Ana (J Biol Chem, 2016)
Annexins are a family of proteins that bind to phospholipids in a calcium-dependent manner. Earlier studies implicated annexin A6 (AnxA6) to inhibit secretion and participate in the organization of the extracellular matrix. We recently showed that elevated AnxA6 levels significantly reduced secretion of the extracellular matrix protein fibronectin (FN). Because FN is directly linked to the ability of cells to migrate, this prompted us to investigate the role of AnxA6 in cell migration. Up-regulation of AnxA6 in several cell models was associated with reduced cell migration in wound healing, individual cell tracking and three-dimensional migration/invasion assays. The reduced ability of AnxA6-expressing cells to migrate was associated with decreased cell surface expression of αVβ3 and α5β1 integrins, both FN receptors. Mechanistically, we found that elevated AnxA6 levels interfered with syntaxin-6 (Stx6)-dependent recycling of integrins to the cell surface. AnxA6 overexpression caused mislocalization and accumulation of Stx6 and integrins in recycling endosomes, whereas siRNA-mediated AnxA6 knockdown did not modify the trafficking of integrins. Given our recent findings that inhibition of cholesterol export from late endosomes (LEs) inhibits Stx6-dependent integrin recycling and that elevated AnxA6 levels cause LE cholesterol accumulation, we propose that AnxA6 and blockage of LE cholesterol transport are critical for endosomal function required for Stx6-mediated recycling of integrins in cell migration.